ENHANCE PRODUCTION OF BLACK TIGER SHRIMP Penaeus monodon POSTLARVAE BY PROBIOTIC BACTERIUM Alteromonas sp. - Haryanti Haryanti; Ketut Sugama; Seiichi Tsumura; Roshitaka Nishijima (Indonesian Fisheries Research Journal, 2001)
Alteromonas sp. (coded as BY-9) bacterium isolated from the coastal water of Gondol Bali, Indonesia was purified and mass produced, then inoculated into the rearing media of penaeus monodon farvae as a probiotic agent.